Characterization of students with high intellectual capacity: the approach in the Portuguese school context and importance of teacher training for their educational inclusion - García-Perales, Ramón; Rocha, Alberto; Aguiar, Ana; Almeida, Ana Isabel S. (Frontiers in Psychology, 2024)
Before checking your proof, please see the instructions below.• Carefully read the entire proof and mark all corrections in the appropriate place, using the Adobe Reader commenting tools (Adobe Help). Do not use the Edit tool, as direct edits to the text will be ignored; annotate your corrections instead. • Provide your corrections in a single PDF file or post your comments in the Production Forum, making sure to reference the relevant query/line number. Upload or post all your corrections directly in the Production Forum to avoid any comments being missed. • We do not accept corrections in the form of edited manuscripts or via email.• Do not provide scanned or handwritten corrections.• Before you submit your corrections, make sure that you have checked your proof carefully as once you approve it, you won't be able to make any further corrections. • To ensure timely publication of your article, please submit your corrections within 48 hours. We will inform you if we need anything else; do not contact us to confirm receipt. Do you need help? Visit our Production Help Center for more information. If you can't find an answer to your question, contact your Production team directly by posting in the Production Forum. NOTE FOR CHINESE-SPEAKING AUTHORS: If you'd like to see a Chinese translation, click on the  symbol next to each query. Only respond in English as non-English responses will not be considered. Translated instructions for providing corrections can be found here.□ Author names -Complete, accurate and consistent with your previous publications.